2021
DOI: 10.21203/rs.3.rs-352249/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SINE jumping contributes to large-scale polymorphisms in the pig genomes

Abstract: Background: Molecular markers based on retrotransposon insertion polymorphisms (RIPs) have been developed and are widely used in plants and animals. Short interspersed nuclear elements (SINEs) exert wide impacts on gene activity and even on phenotypes. However, SINE RIP profiles in livestock remain largely unknown, and not be revealed in pigs. Results: Our data revealed that SINEA1 displayed the most polymorphic insertions (22.5% intragenic and 26.5% intergenic), followed by SINEA2 (10.5% intragenic and 9% int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…This may be because there is less chance that the retrotransposons inserted into the conserved region will be retained after insertion [53]. Furthermore, our recent study revealed that young SINEs generated a large-scale SINE RIPs occurrence (over 35,000) with an even distribution across chromosomes (14.5 Mb) [54], indicating that SINE may play important roles in genomic variation and evolution in pigs. Here, we found that out of a total of five RIPs confirmed by PCR in the GHR and IGF1 genes, four were derived from SINE insertions, providing additional evidence that SINEs may have an impact on genetic variations in pig.…”
Section: Discussionmentioning
confidence: 94%
“…This may be because there is less chance that the retrotransposons inserted into the conserved region will be retained after insertion [53]. Furthermore, our recent study revealed that young SINEs generated a large-scale SINE RIPs occurrence (over 35,000) with an even distribution across chromosomes (14.5 Mb) [54], indicating that SINE may play important roles in genomic variation and evolution in pigs. Here, we found that out of a total of five RIPs confirmed by PCR in the GHR and IGF1 genes, four were derived from SINE insertions, providing additional evidence that SINEs may have an impact on genetic variations in pig.…”
Section: Discussionmentioning
confidence: 94%